Short surface waves in the Canadian Arctic in 2007 and 2008. Issue 7 (30th July 2013) - Bogucki, D. J.; Drennan, W. M.; Woods, S.; Gremes‐Cordero, S.; Long, D. G.; Mitchell, C.
Abstract : [1] We have collected time series data of short oceanic waves as a part of the International Polar Year (IPY) 2007–2008. Using a shipboard laser wave slope (LAWAS) system operating at 900 nm, we have obtained wave slopes measurements up to 60 rad m −1 wave number. We have compared our in situ wave slopes with collocated and concurrent high‐resolution upwind Normalized Radar Cross Sections (NRCS) collected by QuikSCAT. The LAWAS measured wave slope spectra were consistent with local wind speeds and QuikSCAT measured NRCS. Our measured short wave mean slopes indicate their enhancement by long waves (0–1 rad m −1 ) at small values of long‐wave slope. Concurrent with wave slope measurements, the strength of the reflected LAWAS light beam was analyzed in terms of the light attenuation coefficient at 900 nm. We have observed a correlation between surface elevation and light attenuation. The mechanism of wave modulated beam attenuation was found to be related to the instantaneous long wave skewness. Key Points: Short wave slopes Inhibiting effect of long waves Normalized Radar Cross Sections